Pengaruh Promosi, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Scarlett Whitening (Studi Kasus Pada Mahasiswa Universitas Victory Sorong) - Rouli Basa Tambunan; Lisma Latuperisa; Andris Novian Burdam (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The purpose of this study was to determine and analyze the effect of promotion, product quality, and price on purchasing decisions on scarlett whitening products, a case study on female students of Victory University Sorong. The approach used in this study is an associative approach. The population in this study was students from Victory University Sorong and the sample set amounted to 65 people. The data collection technique in this study used questionnaire techniques. Data analysis techniques in this study use Classical Assumption Test, Multiple Regression, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Promotion t test result 0.447, Product Quality 0.02 and Price 0.302. Partially, Promotions and Prices do not have a significant influence on Purchasing Decisions, while Product Quality has a significant influence on Purchasing Decisions. The significant result of the F test is 0.000, so simultaneously promotion, product quality and price have a significant influence on the purchase decision of scarlett whitening products in Victory University Sorong Students.